Impact of the implementation of the Lean Six Sigma process within Moroccan environmental SMEs - El Attaoui Zuhair (E3S Web of Conferences, 2023)
Lean Six Sigma is a management approach used to improve the efficiency, quality and performance of processes within companies. When applied to environmental businesses in Morocco, Lean Six Sigma can bring several significant benefits. Lean Six Sigma aims to eliminate waste, inefficiencies and non-essential processes. By applying it to Moroccan environmental companies, it is possible to optimize operations, improve productivity and reduce costs. That can contribute to more efficient use of resources and better management of projects. Environmental companies have the primary mission of minimizing their impact on the environment. Applying Lean Six Sigma can help identify sources of pollution, reduce waste, improve energy efficiency and promote sustainable practices. That helps build their environmental credibility and meet stakeholder expectations. Lean Six Sigma emphasizes customer satisfaction and product or service quality. By integrating this approach, Moroccan environmental companies can improve their production processes, eliminate defects and errors, and provide better quality products and services to their customers. That can promote customer loyalty and increase their competitiveness in the market. The application of Lean Six Sigma within environmental companies in Morocco can bring significant benefits, such as improved operational efficiency, reduction of environmental impacts, improving the quality of products and services, strengthening the culture of continuous improvement and developing employee skills. This is the case that we have dealt with in This article in order to measure the Impact of the implementation of the Lean Six Sigma process within Moroccan environmental SMEs. By adopting That approach, Moroccan environmental companies can strengthen their competitiveness, environmental sustainability and ability to meet stakeholder expectations.